2017
DOI: 10.1002/anie.201707510
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Quantum Dots Used for Boosting Light Harvesting in Organic Photovoltaics

Abstract: Although organic photovoltaic devices (OPVs) have been investigated for more than two decades, the power conversion efficiencies of OPVs are much lower than those of inorganic or perovskite solar cells. One effective approach to improve the efficiency of OPVs is to introduce additives to enhance light harvesting as well as charge transportation in the devices. Here, black phosphorus quantum dots (BPQDs) are introduced in OPVs as an additive. By adding 0.055 wt % BPQDs relative to the polymer donors in the OPVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 38 publications
2
100
0
Order By: Relevance
“…However,t he absorption spectra for the ternary blends including increasing amounts of QDs (from 0t o 20 wt %), as shown in the Supporting Information, Figure S3a, reveals that the absorption characteristics of the BHJ thin-films barely change with the addition of QDs,even up to 20 wt %. This is most likely due to the high absorption coefficients of the organic components, [36,37] the fact that scattering effects like those reported in other hybrid systems are not present, [14] and the comparatively low density of QDs within the active layer. Therelative energy band positions of the components of the device,a se stimated by cyclic voltammetry (Supporting Information, Figure S3 and Table S1), are summarized in Figure 1d.I nterestingly,t he ternary blend displays an asymmetric cascade alignment wherein QDs could potentially mediate hole transfer from the PC 71 BM towards the PTB7-Th, but not the electron transfer from the PTB7-Thtothe PC 71 BM.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However,t he absorption spectra for the ternary blends including increasing amounts of QDs (from 0t o 20 wt %), as shown in the Supporting Information, Figure S3a, reveals that the absorption characteristics of the BHJ thin-films barely change with the addition of QDs,even up to 20 wt %. This is most likely due to the high absorption coefficients of the organic components, [36,37] the fact that scattering effects like those reported in other hybrid systems are not present, [14] and the comparatively low density of QDs within the active layer. Therelative energy band positions of the components of the device,a se stimated by cyclic voltammetry (Supporting Information, Figure S3 and Table S1), are summarized in Figure 1d.I nterestingly,t he ternary blend displays an asymmetric cascade alignment wherein QDs could potentially mediate hole transfer from the PC 71 BM towards the PTB7-Th, but not the electron transfer from the PTB7-Thtothe PC 71 BM.…”
Section: Resultsmentioning
confidence: 93%
“…To ac onsiderably lesser extent, inorganic semiconductor nanoparticles or quantum dots (QDs) have also been explored as ternary components in BHJ OSCs.I nitial reports demonstrated that the incorporation of well-known semiconductor QDs such as colloidal CdSe [11] or core-shell CuInS 2 /ZnS [12] into conventional OSCs yielded rather modest amelioration of PCE. Overcoming the electrically insulating nature of the aliphatic capping ligands typically present in colloidally-synthesized QDs via ligand engineering has advanced the performance of the standard inorganic QD additives, [13] and in the last few years other nanoparticle additives (for example,l igand-free C 3 N 4 QDs, [10] black phosphorous QDs [14] and antimonene quantum sheets [8] )have also shown to improve the PCE of BHJ OSCs.However,one class of emerging QDs (that is,t he inorganic lead halide perovskite QDs) have not yet been explored for use as ternary components in BHJ OSCs,d espite their excellent optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, thin-layered BP has a reported HOMO level of 5.32 eV, [14] and is therefore expected to reduce the hole injection barrier between PEDOT:PSS and CsPbBr 3 . As mentioned above, thin-layered BP has a reported HOMO level of 5.32 eV, [14] and is therefore expected to reduce the hole injection barrier between PEDOT:PSS and CsPbBr 3 .…”
Section: Perovskite Light-emitting Diodesmentioning
confidence: 97%
“…Black phosphorus (BP) has recently received considerable attention due to high hole and electron mobilities (≈1000 cm 2 V −1 s −1 ) and tunable direct bandgap varying from ≈0.3 eV (bulk) to ≈2 eV (monolayer) . Few‐layer BP or BP quantum dots (BPQDs) have been used to modify ETL, or doped in OSCs as third components to enhance device performance . For example, Yan and co‐workers reported that few‐layer BP can be used to modify ETL in OSCs, and PCEs of the BP‐incorporated OSCs were improved from 7.37% to 8.18% .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yan and co‐workers reported that few‐layer BP can be used to modify ETL in OSCs, and PCEs of the BP‐incorporated OSCs were improved from 7.37% to 8.18% . They also introduced BPQDs in OSCs as third component to boost light harvesting and improve PCE to ≈10%, as a result of the strong broadband light absorption and scattering of the BPQDs . Chen and co‐workers used BPQDs as morphology modifier, a higher fill factor (FF) of 0.73 was obtained and PCE was improved from 11.4% to 12.2% .…”
Section: Introductionmentioning
confidence: 99%